Behaviour of Hop-derived Branched-chain Esters During Fermentation and Unique Characteristics of Huell Melon and Ekuanot (HBC366) Hops: A preliminary report of some of this work was given at the 35th Congress of the European Brewery Convention, Porto, Portugal, 24-28 May, 2015 - Takoi, Kiyoshi; Itoga, Yutaka; Koie, Koichiro; Takayanagi, Junji; Kaneko, Takeshi; Watanabe, Takayuki; Matsumoto, Ichiro; Masahiro, Masahiro (BrewingScience, 2018)
In this study, hop-derived isobutyric esters (isobutyl isobutyrate, isoamyl isobutyrate, and 2-methylbutyl isobutyrate) and ethyl esters of branched-chain fatty acids (ethyl isobutyrate, ethyl isovalerate, and ethyl 2-methylbutyrate) have been focused on. The wort, green beer, and finished beer samples hopped with total 42 hop varieties were analyzed and compared. Of the three isobutyric esters, 2-methylbutyl isobutyrate is most dominant component. All isobutyric esters gradually decreased during fermentation. All ethyl esters of branched-chain fatty acids were almost absent in wort and gently increased during total fermentation period, except for the fermentation using Huell Melon hops. Surprisingly, the wort made by Huell Melon hops only contained ethyl isobutyrate and ethyl 2-methylbutyrate at relatively high levels. On the other hand, the concentrations of all three ethyl esters in the Ekuanot (HBC366) beer were at relatively high levels and ethyl isovalerate was most dominant component. In addition, it is suggested that a part of 2-methylbutyl isobutyrate (threshold in beer, 78 μg/L) could be transesterificated to ethyl isobutyrate (threshold in beer, 6.3 μg/L). The transesterification between these esters might be an important reaction for hop aromas in beer. From this study, it is concluded that hop-derived various esters including branched-chain structures might be very important contributors to hop varietal aromas, having two roles, their own fruity flavours and precursors of ethyl esters of branched-chain fatty acids.